Strange particle production in proton–proton collisions at √s=0.9 TeV with ALICE at the LHC - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (The European physical journal. C, Particles and fields, 2011)
The production of mesons containing strange quarks (K0S, φ) and both singly and doubly strange baryons (Λ, Λ¯¯¯¯, and Ξ−+Ξ¯¯¯¯+) are measured at mid-rapidity in pp collisions at s√ = 0.9 TeV with the ALICE experiment at the LHC. The results are obtained from the analysis of about 250 k minimum bias events recorded in 2009. Measurements of yields (dN/dy) and transverse momentum spectra at mid-rapidity for inelastic pp collisions are presented. For mesons, we report yields (〈dN/dy〉) of 0.184±0.002(stat.)±0.006(syst.) for K0S and 0.021±0.004(stat.)±0.003(syst.) for φ. For baryons, we find 〈dN/dy〉=0.048±0.001(stat.)±0.004(syst.) for Λ, 0.047±0.002(stat.)±0.005(syst.) for Λ¯¯¯¯ and 0.0101±0.0020(stat.)±0.0009(syst.) for Ξ−+Ξ¯¯¯¯+. The results are also compared with predictions for identified particle spectra from QCD-inspired models and provide a baseline for comparisons with both future pp measurements at higher energies and heavy-ion collisions.
*The ALICE Collaboration: K. Aamodt, V. Anguelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, D. Lohner, X.G. Lu, J. Mercado Perez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, S. Vallero, B. Windelband [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 17.02.2022